A simulation study of material handling systems - Kunhal Rajesh Lakhiani. (2013)
Automated Material Handling Systems have long been known to be of great utility to small and medium production houses, air and sea cargo depots and other inventory control centers. CEOs and other high-level managers are however apprehensive about the added costs of running these systems, the probabilities of failures and repair and maintenance mechanisms. This project creates a simulation model of a simple material handling system with three stations served by a single Automated Guided Vehicle (AGV). This simulation is created using the software called Arena by Rockwell Automation that uses the SIMAN simulation language. The software automatically generates the results when the simulation runs to completion. Upon analysis of the results of the simulation, this project proves that in spite of added initial costs, an automated material handling system is profitable in the long run.